IMPROVEMENT OF READING SKILLS WITH IMAGES IN CLASS 2 SDN PEMAMPON 1 JOMBANG - Alya Insan Nabila; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Media is a learning support component whose function is very crucial in making it easier for teachers to convey material to students, including Indonesian content. The content of the Indonesian language itself consists of several aspects of skills, one of which is reading skills. Skills are very important to master, because through these reading skills, students will be able to obtain information from reading sources that are read. This study aims to improve students' reading skills using pictures in grade 2 SDN Pengampon 1 Jombang. This type of research is classroom action research (CAR). The research subjects were 12 students of class 2 SDN Pengampon 1 Jombang. For data collection techniques, namely by observation, interviews and documentation. The results showed that in the pre-cycle only 25% of students completed, then there was an increase of 41.7% in the first cycle and in the second cycle it increased to 83.3%, meaning that learning through image media can be used as an effort or method in students' reading skills.